Functionalization of graphene at the organic/water interface. Issue 2 (4th December 2014) - Toth, Peter S.; Ramasse, Quentin M.; Velický, Matěj; Dryfe, Robert A. W.
Abstract : A simple method for the deposition of noble metal (Pd, Au) nanoparticles on a free-standing chemical vapour deposited graphene monolayer is reported. Metal deposition can proceed using either spontaneous or electrochemically-controlled processes. The resultant nanoclusters are characterized using atomic force and electron microscopy techniques, and mapping mode Raman spectroscopy. Abstract : A simple method for the deposition of noble metal (Pd, Au) nanoparticles on a free-standing chemical vapour deposited graphene (CVD GR) monolayer is reported. The method consists of assembling the high purity CVD GR, by transfer from poly (methyl methacrylate) (PMMA), at the organic/water interface. Metal deposition can then proceed using either spontaneous or electrochemically-controlled processes. The resultant graphene-based metal nanoclusters are characterized using atomic force and electron microscopy techniques, and the location of the nanostructures underneath the graphene layer is determined from the position and the intensity changes of the Raman bands (D, G, 2D). This novel process for decoration of a single-layer graphene sheet with metal nanoparticles using liquid/liquid interfaces opens an alternative and useful way to prepare low dimensional carbon-based nanocomposites and electrode materials.